Design and Fabrication of an Improved Single-Column Chromatographic Separation Process - B. Medi; M.-K. Kazi (Iranian Journal of Chemical Engineering)
In this work, an improved single-column chromatographic (ISCC) separation process is proposed. The term `improved' refers to both conceptual and physical modifications compared to the available single-column processes, including a novel fraction collection scheme and allowing overlapped peaks from adjacent cycles. Also the fraction collection mechanism was modified in order to facilitate online monitoring. Another advantage of the ISCC process is its large degree of freedom as injection volume, cycle time, solvent flow rate, feed concentration, and fraction-collection intervals can all be decision variables in this process. The experimental implementation and validation is covered in this work. The results indicate successful operation of the ISCC process and accompanying peripherals for the separation of guaifenesin enantiomers. In particular, the tests confirmed the integrity of the online monitoring system and proved the capability of the process for 98% purification of the tested enantiomers with an advantageously shorter cycle time, which results in higher productivity.